2018
DOI: 10.1186/s12905-018-0598-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical activity on fasting blood glucose and lipid profile among low income housewives in the MyBFF@home study

Abstract: BackgroundRegular physical activity has always been strongly recommended for good cardiovascular health. This study aimed to determine the effect of physical activity on fasting blood glucose and lipid profile among low income housewives in Klang Valley.MethodsData of 328 eligible housewives who participated in the MyBFF@Home study was used. Intervention group of 169 subjects were provided with an intervention package which includes physical activity (brisk walking, dumbbell exercise, physical activity diary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…But this MR study confirmed the findings from a Japanese prospective study showing that excessive vigorous-intensity activities might not be beneficial or even disadvantageous for prevention of hemorrhagic stroke for Japanese people [42]. Likewise, there was few significant effect of physical activity on lipid profiles among groups in intervention studies, which was consistent with our null finding [43,44]. Further investigations are warranted to elucidate the potential association between physical activity and different stroke subtypes or lipids.…”
Section: Discussionsupporting
confidence: 91%
“…But this MR study confirmed the findings from a Japanese prospective study showing that excessive vigorous-intensity activities might not be beneficial or even disadvantageous for prevention of hemorrhagic stroke for Japanese people [42]. Likewise, there was few significant effect of physical activity on lipid profiles among groups in intervention studies, which was consistent with our null finding [43,44]. Further investigations are warranted to elucidate the potential association between physical activity and different stroke subtypes or lipids.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported, that three-quarter of cardiovascular deaths can be prevented by embracing healthy lifestyle changes 13 , including adequate physical activity. Evidence suggests that regular physical activity may have beneficial effects on blood glucose control 1 , 13 17 and glycemic variability 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary behavior may be a critical determinant of health, independent of physical activity [10,11]. Sedentary lifestyle and physical inactivity are common practices worldwide and are associated with a wide range of chronic diseases and premature death [12,13]. Although inactivity is known to be harmful, almost one-third of the world's population remains inactive, posing a great risk for public health [14].…”
Section: Introductionmentioning
confidence: 99%